ANALISIS DASAR MENUNTUT PENGGANTIAN BIAYA DALAM GUGATAN PEMBATALAN PERSIAPAN ACARA PERKAWINAN DALAM PUTUSAN NOMOR: 82/Pdt.G/2014/PN.MKS - Patricia Janice; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2019)
This research aims to provide information about existing law for one-sided breach of promise of marriage in Putusan Nomor 82/Pdt.G/2014/PN. Mks and to show that the defendant’s conduct of breaching the promise of marriage is a violation of law instead of a default. The defendant’s breach of promise of marriage, according to the plaintiff, brings material loss and shame because she is a doctor widely known in the society and part of the nobility in Tanah Toraja. This research/case shows that immaterial damage claim cannot be sustained in the context of default because damage compensation in a case of default consists of fee, loss, and interest. Immaterial damage claim can only be sustained in the context of violation of law and the judge should refer to article 1365 KUHPerdata about Violation of Law because the breach of promise of marriage is against the norm of propriety and morality in the society. In Putusan Mahkamah Agung RI No. 522 K/Sip/1994, Putusan Mahkamah Agung RI No 3191 K/Pdt/1984 dated 8 February 1986, and Putusan Mahkamah Agung RI No 3277 K/Pdt/2000 dated 18 July 2003, it was ruled that breach of promise of marriage is a violation of law.